Single injection of basic fibroblast growth factor to treat severe vocal fold lesions and vocal fold paralysis. (6th May 2015) - Kanazawa, Takeharu; Komazawa, Daigo; Indo, Kanako; Akagi, Yusuke; Lee, Yogaku; Nakamura, Kazuhiro; Matsushima, Koji; Kunieda, Chikako; Misawa, Kiyoshi; Nishino, Hiroshi; Watanabe, Yusuke
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis Severe vocal fold lesions such as vocal fold sulcus, scars, and atrophy induce a communication disorder due to severe hoarseness, but a treatment has not been established. Basic fibroblast growth factor (bFGF) therapies by either four‐time repeated local injections or regenerative surgery for vocal fold scar and sulcus have previously been reported, and favorable outcomes have been observed. In this study, we modified bFGF therapy using a single of bFGF injection, which may potentially be used in office procedures. Study Design Retrospective chart review. Methods Five cases of vocal fold sulcus, six cases of scars, seven cases of paralysis, and 17 cases of atrophy were treated by a local injection of bFGF. The injection regimen involved injecting 50 µg of bFGF dissolved in 0.5 mL saline only once into the superficial lamina propria using a 23‐gauge injection needle. Two months to 3 months after the injection, phonological outcomes were evaluated. Results The maximum phonation time (MPT), mean airflow rate, pitch range, speech fundamental frequency, jitter, and voice handicap index improved significantly after the bFGF injection. Furthermore, improvement in the MPT was significantly greater in patients with (in increasing order) vocal fold atrophy, scar, and paralysis. The improvement in the MPT among all patients was significantly correlated with age; the MPT improved more greatly in younger patients. Conclusions Regenerative treatments by bFGF injection—even a single injection—effectively improve vocal function in vocal fold lesions. Level of Evidence 4 Laryngoscope, 125:E338–E344, 2015